Ventrolateral Partial Dorsal Root Entry Zone Rhizotomy for Occipital Neuralgia - Serge Rasskazoff; Anthony M Kaufmann (Pain Research and Management)
OBJECTIVE AND IMPORTANCE: Medically refractory occipital neuralgia (ON) has been treated with a variety of neuroablative procedures. The present case report supports the effectiveness of ventrolateral partial rhizotomy (pVL-DREZ) of the C1 to C3 cervical dorsal roots, a relatively unknown procedure.